PENAPISAN VIRTUAL BERBASIS STRUKTUR DARI DATABASE BAHAN ALAM ZINC SEBAGAI INHIBITOR BRUTON TYROSINE KINASE - Fauzan Zein Muttaqin; Wayan Ayu Puje Astuti; La Ode Aman; Ellin Febrina; Aiyi Asnawi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Bruton’s tyrosine Kinase (BTK) plays a critical role in many cellular signalling pathways making it a potential target to treat autoimmune diseases and cancer. In this study, we have implemented structure-based virtual screening against natural product ZINC database by using pharmacopore model followed by molecular docking to identified the inhibitor of BTK (PDB ID 6E4F). By using structure based pharmacophore, a four-point pharmacophore hypothesis was derived, with three hydropobic, one aromatic rings, four hydrogen bond acceptor and nine hydrogen bond donor. Screening of 12 natural product ZINC databases (151,837 compounds) against pharmacophore returned 1,345 hits with matching chemical features of 58.81. Docking these hits against the ATP-binding site of the BTK kinase domain through a virtual screening docking-based by using vina wizard and autodock wizard (PyRx 8.0) returned 148 and 75 hits, respectively. Three hit compounds with high affinity towards BTK were identified, and it could be used as a potent lead molecule for designing BTK inhibitor.